EFFORTS TO IMPROVE THE COMMUNITY'S UNDERSTANDING REGARDING ILLEGAL ONLINE LOANS ACCORDING TO A SHARIA ECONOMIC LAW : Perspective In Muara Sugih Village - Chastuti Alwallyah; Muhammad Edwinsyah; Oki Sapitri Menghayati, S.E., M.E (Al-Iqtishadiah: Jurnal Hukum Ekonomi Syariah, 2023)
This research aims to explore the public's understanding of illegal online loans from the perspective of Sharia economic law in Muara Sugih Village, Tanjung Lago District, Banyuasin Regency. Illegal online lending has become a serious problem in various regions of Indonesia, with significant economic and social impacts. Especially in the context of rural communities such as Muara Sugih Village, where limited access to information and legal regulations can be a risk factor. This research uses a qualitative approach with interview, observation and document analysis methods to collect data from the local community. The results of this research indicate that the majority of the people of Muara Sugih Village have limited understanding about illegal online loans and their lack of knowledge about Sharia economic law. Factors such as urgent economic needs and the lack of halal financing alternatives influence participation in illegal online lending. To increase public understanding, efforts that need to be made include education about Sharia economic law, the risks of illegal online loans, and financing alternatives that comply with Sharia principles. Local governments and social institutions can also play an active role in providing training and education to the public about the negative impacts of illegal online loans as well as solutions that are in accordance with religious values ​​and Sharia economic law. With a better understanding of this issue, the people of Muara Sugih Village can make wiser decisions in managing their finances in accordance with the principles of Sharia economic law.